2008
DOI: 10.1002/pst.331
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of dichotomization

Abstract: Dichotomization is the transformation of a continuous outcome (response) to a binary outcome. This approach, while somewhat common, is harmful from the viewpoint of statistical estimation and hypothesis testing. We show that this leads to loss of information, which can be large. For normally distributed data, this loss in terms of Fisher's information is at least 1-2/pi (or 36%). In other words, 100 continuous observations are statistically equivalent to 158 dichotomized observations. The amount of information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
178
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(184 citation statements)
references
References 20 publications
5
178
0
1
Order By: Relevance
“…Several studies 16,17 have demonstrated that 100 continuous observations are statistically equivalent to at least 157 dichotomized observations. Selvin 18 derives a formula to calculate the efficiency loss due to categorizing a continuous variable.…”
Section: Problems With Dichotomizationmentioning
confidence: 99%
“…Several studies 16,17 have demonstrated that 100 continuous observations are statistically equivalent to at least 157 dichotomized observations. Selvin 18 derives a formula to calculate the efficiency loss due to categorizing a continuous variable.…”
Section: Problems With Dichotomizationmentioning
confidence: 99%
“…Dichotomising variables reduces power, can bias estimates, and can increase false positives. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] To illustrate this point, Figure 2 shows data for 50 samples that have a correlation of 0.4. These are naturally analysed with a Pearson correlation or linear regression (solid line), both of which give p = 0.002 for the association.…”
Section: Don't Dichotomise or Bin Continuous Variablesmentioning
confidence: 99%
“…There has also been interest in promoting the analysis of continuous rather than dichotomous measures in clinical trials and preclinical research. 38 In AKI, power analysis would be on the basis of the anticipated changes in actual creatinine values rather than setting an artificial dichotomy for what is deemed to be a clinically important effect (such as a 50% reduction in eGFR). This would increase the statistical power of a study without requiring larger numbers.…”
Section: Common Concerns About Preclinical Study Design and Reportingmentioning
confidence: 99%
“…However, alternative approaches for statistical analysis on the basis of the use of continuous versus dichotomous end point variables (such as creatinine) could be used to mitigate the effect of these requirements of research costs. 38 Other problems will be even more difficult to address, and potential solutions will be less obvious. For example, calling for the publication of negative results is unquestionably good for the science community at large but consumes an individual scientist's time and resources with limited academic reward.…”
Section: Recommendations Implementation and Challengesmentioning
confidence: 99%